Assessment of Diabetic Cardiomyopathy by Cardiovascular Magnetic Resonance T1 Mapping: Correlation with Left-Ventricular Diastolic Dysfunction and Diabetic Duration. (16th July 2017) - Shang, Yongning; Zhang, Xiaochun; Leng, Weilling; Chen, Liu; Lei, Xiaotian; Zhang, Tianjing; Greiser, Andreas; Liang, Ziwen; Wang, Jian
Abstract : Purpose . To quantify extracellular matrix expansion with the cardiovascular magnetic resonance (CMR) T1 mapping technique and the derived extracellular volume fraction (ECV) in diabetic cardiomyopathy (DbCM) patients and to detect the relationship among ECV, duration of diabetes, and diastolic function. Materials . Thirty-eight patients with diabetic cardiomyopathy (20 males, age 54.6 ± 8.6 years) and thirty-two matched normal controls (15 males, age 51.4 ± 13.6 years) were prospectively enrolled. All of them were scanned by T1 mapping to obtain the native and postcontrast T1 values of myocardium and blood, and ECV was calculated accordingly. All patients also underwent transthoracic echocardiographic tissue Doppler imaging to assess left-ventricular diastolic function. Results . There was a significant difference in ECV between the two groups (DbCMs 30.4 ± 2.9% versus controls 27.1 ± 2.4%, P < 0.001 ). The duration of diabetes was positively and strongly associated with ECV (R = 0.539, P = 0.0005 ). There was also a significant difference in ECV (P ≤ 0.001 ) among four groups (A, controls; B, DbCM patients with duration of diabetes <5 years; C, 5–10 years; and D, >10 years). ECV was negatively associated with LV E'/A' (R = − 0.403, P = 0.012 ). Conclusion . CMR T1 mapping can reflect myocardial extracellular matrix expansion in DbCM and can be a powerful technique for the early diagnosis of DbCM.